2019
DOI: 10.13057/biodiv/d201024
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compound profiles and cytotoxicity in essential oils from rhizome of Curcuma aeruginosa and Curcuma zanthorrhiza

Abstract: Abstract. Fitria R, Seno DSH, Priosoeryanto BP, Hartanti, Nurcholis W. 2019. Volatile compound profiles and cytotoxicity in essential oils from rhizome of Curcuma aeruginosa and Curcuma zanthorrhiza. Biodiversitas 20: 2943-2948. Cancer becomes one of the uncontagious diseases that occupy the top position in the cause of human death under 70 years in the world. Breast cancer is the most widely experienced cancer by women. The aim of this study was to obtain cytotoxic activity essential oil of Curcuma aeruginosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…(Yuandani et al 2021). Several studies reported pharmacological activities from these plants, including anticancer, antidiabetic, antimicrobial, and antioxidant properties (Akarchariya et al 2017;Nurcholis et al 2017;Nurcholis et al 2018;Fitria et al 2019). This demonstrates the significance of these plants as potential Indonesian medicinal herbs.…”
Section: Introductionmentioning
confidence: 86%
“…(Yuandani et al 2021). Several studies reported pharmacological activities from these plants, including anticancer, antidiabetic, antimicrobial, and antioxidant properties (Akarchariya et al 2017;Nurcholis et al 2017;Nurcholis et al 2018;Fitria et al 2019). This demonstrates the significance of these plants as potential Indonesian medicinal herbs.…”
Section: Introductionmentioning
confidence: 86%
“…The carminative in the digestive system disorder had the highest use reports from these ethnic groups. This was supported by the property of volatile oils in the Zingiberaceae, helping to relieve gas in the alimentary tract (Fitria et al 2019;Information 2016;Li et al 2013).…”
Section: Use Categoriesmentioning
confidence: 98%
“…For the northern part, it was used by many ethnic groups to treat postpartum nervous, e.g., H'tin (Pongamornkul et al 2017), Karen (Pongamornkul et al 2017), Lawa (Songsangchun 2015), and Shan (Pongamornkul et al 2017). However, although using these plants to treat the postpartum disorder is common among ethnic people in Thailand, it was rarely found in other countries (Fitria et al 2019;Fathir et al 2021).…”
Section: Use Categoriesmentioning
confidence: 99%
“…The content of temulawak consists of curcumin and xanthorrhizol [23]. Based on reports by Cheah et al [11] and Fitria et al [24] stated that curcumin and xanthorrhizol compounds can suppress the growth of breast cancer accompanied by a hepatoprotective effect. The AST enzyme activity values in the treatment group and DMBA group had values that were above the normal group values.…”
Section: Groupmentioning
confidence: 99%